2016
DOI: 10.1007/s00438-016-1248-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and functional analysis of the TIFY gene family in response to drought in cotton

Abstract: Jasmonates control many aspects of plant biological processes. They are important for regulating plant responses to various biotic and abiotic stresses, including drought, which is one of the most serious threats to sustainable agricultural production. However, little is known regarding how jasmonate ZIM-domain (JAZ) proteins mediate jasmonic acid signals to improve stress tolerance in cotton. This represents the first comprehensive comparative study of TIFY transcription factors in both diploid A, D and tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…Segmental duplications were found in the CsTIFY family, mainly in the CsZML and CsJAZ subfamilies. Our results agree with the duplication phenomenon identified within the TIFY family, supporting the notion that duplication events play an important role in the evolution and expansion of the TIFY family in plants [6][7][8]33]. CsTIFY members in the same subfamily generally possessed a similar gene structure and shared the same distribution of conserved domain patterns, indicating the strong correlation between phylogeny and intron/exon diversification and conserved domain patterns within CsTIFY.…”
Section: Discussionsupporting
confidence: 89%
“…Segmental duplications were found in the CsTIFY family, mainly in the CsZML and CsJAZ subfamilies. Our results agree with the duplication phenomenon identified within the TIFY family, supporting the notion that duplication events play an important role in the evolution and expansion of the TIFY family in plants [6][7][8]33]. CsTIFY members in the same subfamily generally possessed a similar gene structure and shared the same distribution of conserved domain patterns, indicating the strong correlation between phylogeny and intron/exon diversification and conserved domain patterns within CsTIFY.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, PtrJAZ5 was dramatically upregulated at early response time points (3 and 6 h) under MeJA treatment. GaJAZ5 was the homologous gene of PtrJAZ5 in Gossypium arboretum; previous research had shown that when GaJAZ5-overexpression lines were treated with exogenous MeJA, the lateral root and root hair were higher in number compared to untreated transgenic lines in cotton [51]. OsJAZ1 could regulate root development by interacting with OsMYC2 through JA signaling in Rice [52].…”
Section: Discussionmentioning
confidence: 99%
“…ENT BINDING 2A, -B and -C, which mediate responses to drought and salinity (Liu et al, 1998), and JAZ proteins, which function as negative regulators of jasmonic acid responses and regulate responses to drought and extremes of temperatures (Chini et al, 2007;Zhao et al, 2016).…”
Section: New Phytologistmentioning
confidence: 99%